2013
DOI: 10.1155/2013/138659
|View full text |Cite
|
Sign up to set email alerts
|

Management of Crown Root Fracture by Interdisciplinary Approach

Abstract: Fracture of tooth after trauma is distressing to a person because of the discomfort and pain due to pulpal injury. Crown root fractures of anterior teeth cause concomitant periodontal injury and there will be concern about appearance, and aesthetics. Management of pulpal and periodontal tissue relieves pain and restoration of tooth form regains patients confidence. Restoration of fractured tooth will be accepted readily if it is minimally invasive, less expensive, and aesthetically acceptable. Reattachment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Tooth mobility and percussion tests were used as diagnostic tests in six 13,15,22,25,28,29 and two articles, 13,29 respectively. In ten of the included articles, only a single straight angled pre‐operative intra‐oral periapical (IOPA) radiograph was taken for the assessment of the extent of fracture 10,12–15,22–25,27 . In addition to an IOPA, an orthopantomograph (OPG) 29 and a soft tissue radiograph 26 were taken in one article each.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tooth mobility and percussion tests were used as diagnostic tests in six 13,15,22,25,28,29 and two articles, 13,29 respectively. In ten of the included articles, only a single straight angled pre‐operative intra‐oral periapical (IOPA) radiograph was taken for the assessment of the extent of fracture 10,12–15,22–25,27 . In addition to an IOPA, an orthopantomograph (OPG) 29 and a soft tissue radiograph 26 were taken in one article each.…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles 10,15,16,24–26,28,29 reported that the fracture line was violating the biological width whereas, in four articles it was mentioned that there was no violation 13,14,22,27 . In two articles, detail regarding the extent of the fracture line was not mentioned 12,23 . The fractured coronal fragment was reported to be detached (avulsed) in two articles (1 case report and a tooth of a case series) 14,27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone graft as autogenic, allogenic, and heterogenic with or without barrier membrane, synthetic materials, platelet rich fibrin gives a good result for ARP [ In contrast to our case, the horizontal fractures are described in the central maxillary incisors in the literature. These conditions lead to aesthetic, functional, and healing problems [16]. According to Andreason et al [4], recovery of root fractures is divided into four different types: a) recovery with hard tissue, b) recovery with conjunctive tissue interposition, c) recovery with bone and conjunctive interposition between the fragments, and d) recovery with granulation tissue between the fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal fractures usually occur in the central maxillary incisors. These fractures subsequently lead to aesthetic, functional, and phonetic problems [ 4 ], and healing from fractures can be complicated. Andreason et al [ 5 ] reported four different types of healing in root fractures: (a) healing with calcified tissue, (b) healing with conjunctive tissue interposition, (c) healing with bone and conjunctive interposition between the fragments, and (d) healing with granulation tissue between the fragments.…”
Section: Introductionmentioning
confidence: 99%